Self-knowledge and its applications in education - Do, Mạnh Cường (Journal of Technical Education Science, 2014)
Self-knowledge is a human fact and a fundamental condition for human beings to fulfill their human calling. It enables them to live a conscious, free and responsible life. ‘Know oneself’ is also a basic premise to know and interact with the world. Without a proper knowledge of the self, it is impossible to know the other properly. Although self-knowledge may appear at the first moment of a human existence, it needs to be developed through all the phases of a human life. Hence the vital role of education in the process of self cognition.The paper starts from some widely recognized psychosocial theories on the subject and then discusses its various applications in education.